Atrial septal defect presenting with Brucella endocarditis - Rahman, A; Burma, O; Felek, S; Yekeler, H (Taylor & Francis as, 2001)
Brucella endocarditis, although a rare complication of brucellosis, is the main case of death attributable to this disease. An atrial septal defect (ASD) presenting with endocarditis in an adult is also extremely rare. We report the case of a male patient who presented with an infective endocarditis and was found to have an ASD. The diagnosis was proven by means of positive serology and isolation of Brucella melitensis from blood cultures and excised vegetation arising from the border of the ASD. The patient was successfully treated by means of excision of the vegetation and specific antibiotic therapy for 3 months.
Keywords: Infective Endocarditis